2000
DOI: 10.1016/s1074-7613(00)00080-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Negative Selection on the T Cell Repertoire Reactive to a Self-Peptide

Abstract: How negative selection shapes a polyclonal population of self-reactive T cells has been difficult to address directly because of the lack of means to isolate T cells reactive to a particular self-peptide. Here, using mice transgenic for the TCR-beta chain of a CTL clone directed against a male-specific peptide, we compared the preimmune repertoire reactive to this peptide in male and female animals. Surprisingly, in the presence of the deleting ligand, as many as 25%-40% of reactive T cells escaped clonal dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
257
3
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(281 citation statements)
references
References 44 publications
18
257
3
3
Order By: Relevance
“…The presence of autoreactive T cells in healthy individuals is a well-known phenomenon and in itself is insufficient to break tolerance (41). Even in the absence of AIRE-regulated ectopic transcription of peripheral Ags in the thymus and a concomitant impairment of negative selection, no disease occurs without a defect in the Treg cell population.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of autoreactive T cells in healthy individuals is a well-known phenomenon and in itself is insufficient to break tolerance (41). Even in the absence of AIRE-regulated ectopic transcription of peripheral Ags in the thymus and a concomitant impairment of negative selection, no disease occurs without a defect in the Treg cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Data from studies using transgenic mice suggested that susceptibility to negative selection is mostly determined by a threshold of avidity, and only low avidity T cells were present in mice expressing the specific antigen. 38 For self-antigens that are not expressed in the thymus at sufficient concentrations to eliminate autoreactive T cells, tolerance mechanisms also exist in the periphery. Using transgenic mouse models, deletion of high-avidity T cells has been described for self-antigens expressed in pancreas 39 or intestine 40 through a process involving cross-presentation of antigen by DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although negative selection deletes strongly self-reactive T cells (1), this process is incomplete. T cells carrying receptors with intermediate and low affinity for self-antigen are routinely released into peripheral lymphoid tissues, where they may become activated, expand and possibly initiate autoimmune disease (2). This process is held in check by several cellular mechanisms, including specialized regulatory T cells (Treg) that suppress immune reactions to self.…”
Section: Introductionmentioning
confidence: 99%